Comparison of sealer penetration of sonic activation versus conventional needle irrigation: a systematic review and meta-analysis of randomized controlled trials - Li Tan; Qiong Liu; Yun Chen; Ya-Qiong Zhao; Jie Zhao; Marie Aimee Dusenge; Yao Feng; Qin Ye; Jing Hu; Ze-; Ying-Hui Zhou; Yue Guo; et al. (BMC, 2022)
Abstract Background Most existing studies comparing the efficiency of sonic irrigation (SI) and conventional needle irrigation (CNI) in increasing the penetration of sealers into dentine tubules are controversial; and this study aimed to determine whether the use of SI can lead to greater sealing ability than CNI, during the root canal treatment. Methods The EMBASE, PubMed, and Cochrane Library databases were used to find confocal laser scanning microscopy studies evaluating percentage and maximum depth of sealer penetration following the use of SI or CNI in mature permanent teeth until October 2022. The critical estimative checklist of randomized controlled trials of the standardized Joanna Briggs Institute was adopted to independently score the quality of each study. The random-effect model for meta-analysis was used to analyse for each canal segment (apical, middle, coronal). The results are shown in the forest plots as weighted mean differences (WMDs) with 95% confidence intervals (95% CIs). Results Ninety-seven articles were included in the preliminary screening, and nine of them were included in this study. Eight studies were included in the meta-analysis.The meta-analysis exhibited great increases in the coronal (WMD: 8.09, 95% CI 2.78-13.40/WMD: 165.32, 95% CI 128.85-201.80), and middle segments (WMD: 8.81, 95% CI 5.76-11.87/WMD: 132.98, 95% CI 68.71-197.25) for the percentage and maximum depth of sealer penetration, respectively. The percentage of sealer penetration in the apical thirds region was nonsignificant (WMD: 4.73, 95% CI − 2.34-11.80). However, the maximum depth of sealer penetration in the apical thirds region was significant (WMD: 121.46, 95% CI 86.55-156.38). Chi-squared analysis revealed heterogeneity scores of 0.0-70.0% and 44.0-90.0% for the percentage and maximum depth of sealer penetration, respectively. Discussion This review verified that SI significantly improves tubular dentin sealer penetration in most areas of the root canal; thus, SI may lead to better filling efficiency and anti-reinfection effects than CNI during and after the root canal therapy. Nevertheless, a large heterogeneity in the current data comparing the irrigation efficiency of SI versus CNI in the apical third of the root canal was found, implying the necessity to standardize root canal irrigation procedures and obtain more accurate results in this area. Trial Registration: INPLASY database (INPLASY202270116).